Physical and genetic characterization of the glucitol operon in Escherichia coli. - Yamada, M (1987)
The glucitol (gut) operon has been identified in the colony bank of Clark and Carbon (A. Sancar and W. D. Rupp, Proc. Natl. Acad. Sci. USA 76:3144-3148, 1979). We subcloned the gut operon by using paCYC184, pACYC177, and pBR322. The operon, which is encoded in a 3.3-kilobase nucleotide fragment, consists of the gutC, gutA, gutB, and gutD genes. The repressor of the gut operon seemed to be encoded in the region downstream from the operon. The gene products of the gut operon were identified by using maxicells. The apparent molecular weights of the glucitol-specific enzyme II (product of the gutA gene), enzyme III (product of the gutB gene), and glucitol-6-phosphate dehydrogenase (product of the gutD gene) were about 46,000, 13,500, and 27,000, respectively, as estimated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis.